Pengembangan e-modul interaktif IPA dasar sebagai media pembelajaran - Mutia, Nur Balqis; Cyntia Pritasari, Ade (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2022)
The Covid-19 pandemic has changed many dimensions of people's lives, including the world of education. Education during the Covid-19 pandemic is carried out remotely to prevent wider transmission. The use of technology for distance learning plays an important role in achieving effective and collaborative learning activities. This study aims to produce a valid and practical learning media in the form of a Basic Science MI/SD e-module to be used during distance learning with the Canva application. The research method used is development research that adapts the ADDIE model. The data collection instruments used were observation sheets, product validation sheets for Basic Science MI/SD e-modules, and student response sheets for the practicality of Basic Science MI/SD e-modules. The results showed that the Basic Science MI/SD e-module was valid, feasible, and practical to use during distance learning activities